High-Value Utilization of Okara: Biotransformation Pathways - MENG Weimin, GAO Yaxin, HU Miao, WEN Wei, ZHANG Pengfei, ZHANG Fengxia, WANG Fengzhong, LI Shuying (Shipin Kexue)
Okara, the major by-product from the production of soybean products, is rich in dietary fiber, protein, fat, vitamins and other nutrients, and functions to regulate the intestinal flora, prevent diabetes, control body mass, prevent and treat cardiovascular diseases. However, there are many problems with okara: high-water content, poor taste and susceptibility to spoilage, restricting its high-value development. Microbial fermentation is a green and safe treatment for okara, which can improve the functional properties and taste and prolong the shelf life, thereby increasing the utilization value. Although the effect of fermentation on the functional properties of okara has been extensively studied, it has not been systematically elaborated and summarized. Therefore, this article focuses on the hotspots in okara fermentation research by means of bibliometrics and visualization analysis. Based on the obtained results, it provides a systematic review on the biotransformation of okara by microbial fermentation, the metabolism pattern of okara nutrient components, the fermentation methods of okara and its application scenarios in foods, aiming at providing a theoretical basis for the value-added utilization and functional development of okara in plant-based foods.